Intention to Purchase Hybrid Cars in India : A Study - Khandelwal, Utkal; Bajpai, Naval; Tripathi, Vikas; Yadav, Seemant (Indian Journal of Marketing, 2016)
This study aimed to measure consumer purchase intention of hybrid cars in India and discussed various factors and previous studies associated with purchase intention of hybrid cars in different nations. The results serve as a reference for automobile companies planning to launch hybrid cars in the near future in India. Five different constructs were extracted from literature for measuring intention to purchase hybrid cars in India, including seeking green products information, self image effects, social value of hybrid car purchase, emissions importance, and social value of green product purchases that is associated with owning a hybrid car in India. Partial least square structural equation modeling was incorporated to establish the relationship model. The results indicate that Indian consumers showed relatively high purchase intention towards hybrid cars. Our analysis found that seeking green product information, social value of hybrid car purchase, and social value of green product purchase is positively associated with hybrid car purchase intention among Indian consumers. However, self image effects and emission importance emerge to be negatively associated with hybrid car purchase intention. Indian consumers are yet to warm up to the idea of purchasing eco friendly cars known as hybrid cars, and it takes a long time to create awareness among Indian consumers towards the advantages of accepting hybrid cars. This study would be helpful for the automobile sector to better understand the various dimensions needed for developing a positive intention towards hybrid cars.